Ecological Education in Southeast Asia Ecocriticism: Ecocritical Approaches to Children’s Literature in Vietnam - Bui Thi Thu Thuy (수완나부미, 2024)
Since the last years of the twentieth century, the approach to children’s literature from ecocriticism has been discussed in academic fora around the world, especially in the US and Europe. In Southeast Asia, with the foundation of the ASEAN Association of Environment and Literature in 2016, there have been scholarly discussions about the capacity of children's literature to enhance ecological awareness in the region. In Vietnam, since the early years of the 21st century, with the increasing reception of ecocriticism from outside, children’s literary works have become the subject of ecocriticism. This article examines scholarly works approaching children's literature in Vietnam, pointing out how they elucidate messages about environmental education. By studying Vietnamese ecocritical scholarship of various types including research, commentaries, and criticism on children’s literature, this article argues that ecological education is a prominent feature in the relationship between ecocriticism and children's literature in Vietnam. As such, Vietnamese ecocriticism of children's literature shares the prominent argument of international materials on children's literature and ecocriticism, particularly in Southeast Asia.